D-Shaped Concrete-Filled Steel Tube Structure in Bridge Engineering - Yuan Liu; Wei Wang; Changqing Wang; Shuosong Bi; Jianming Zhu (Advances in Civil Engineering)
With the continuous progress of the construction industry, the requirements for concrete in the bridge engineering are getting higher and higher. This research mainly discusses the detection of D-shaped concrete-filled steel tube structure in bridge engineering. In this study, the D-shaped concrete-filled steel tube member was used as the research object, and the load-displacement curve of the D-shaped concrete-filled steel tube compression-bending member was analyzed by the fiber model program. In the determination of the bonding state of the concrete-filled steel tube interface, in order to avoid the impact of mechanical and manual vibrating and the difference in concrete pouring methods on the test, the study uses C60 self-compacting microexpansion concrete. While pouring the specimens, three sets of cube specimens with a side length of 100 mm are reserved to determine the mechanical properties of the concrete simultaneously. In the temperature shock measurement of the concrete-filled steel tube specimen, the concrete-filled steel tube specimen was placed in a resistance heater during the simulated heating stage and heated to 20°C, 40°C, 60°C, and 80°C at room temperature. When measuring the mechanical properties of the specimen under the axial load, the specimen is heated from room temperature to the temperature of the entire section to reach 20°C, 40°C, 60°C, and 80°C. After preloading, the load of each level is 10t for continuous operation. Load and record the strain of the steel pipe and concrete under each load. If only the radial effect of the steel tube on concrete is considered, the temperature of 11°C, 20°C, and 80°C is the best ambient temperature. The results show that the D-shaped steel tube concrete interface state can provide a certain theoretical and experimental reference for the optimization of the steel tube concrete interface, ensuring the long-term working performance of the steel tube concrete under the harsh environment.